IMPROVED VOLTAGE OF CASCADED INVERTERS USING SINE QUANTIZATION PROGRESSION - Bambang Sujanarko; Mochamad Ashari; Mauridhi Hery Purnomo (Universitas Ahmad Dahlan, 2010)
The previous methods of cascaded multilevel inverter (CMLI) can improve power quality but the methods have low voltage output if the DC voltages limited by the voltage rating of power semiconductor. To improve the amplitude of CMLI output voltage, this paper proposes a new DC voltage progression. The progression based on sine quantization method (SQM), which determines a sequence of DC voltages from discrete amplitudes of sine wave function. The method also collaborates with step equal residual area method (SERAM) to minimized total harmonics distortions (THD). A single-phase CMLI that consist four H-Bridges simulated and implemented to verify the methods. Amplitude output voltage and THD results of simulations and experiments indicate that the sine quantization progression produce the highest output voltage than other DC voltage progressions, with power quality or THD in the accepted region. The amplitude of output voltage have linier function with amplitude equal 0.6665 times of H-Bridges numbers and have exponential function of THD with value below 5%.